PEMETAAN DIGITAL UNTUK MENDUKUNG PENGEMBANGAN KAWASAN WISATA PECINAN JAMBLANG - Achmad Aprizal Ghozali; Bagus Tri Andana; Cintiya Dewanti Santoputri; Latifah Nur Azizah; Dave Vian Nurzaqi; Mohamad Nurfian Rachmat; Gyanrahma Indrajid Sofwan; Roswati; Felicia Lodhita; Cindrawaty Lesmana; Elliati Djakaria; Mohamad Irfan Nurrachman; Miky Endro Santoso; Tessa Eka Darmayanti; Krismanto Kusbiantoro; Leonardo; Ferlina Sugata (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2022)
Jamblang is a village near Jamblang River in Depok District, Cirebon Regency. The area has a long history of Overseas Chinese Settlements. The Chinese Heritage in Jamblang Village becomes one of the local potentials that can be developed for tourism purposes. The Chinatown in Jamblang Village has not been well-organized and well-developed. This community service program was aimed at collecting data to develop Jamblang Village as a Chinatown tourism area. The program was divided into four phases, i.e.: phase of screening, phase of data collection, phase of data management, and phase of evaluation and follow-up. Survey and area mapping were done in collaboration with the local community as part of data and aspiration collection. Data were collected through an interview, survey, observation, direct measurement, aerial photography using Unmanned Aerial Vehicle and exhibition. The results of data collection were analyzed and processed into valuable findings, such as: Jamblang Chinatown digital mapping, and old building assessment. The findings were intended to support Jamblang as Chinatown Tourism Area.